Belarusian Nation-Building : in Times of War and Revolution - Kasmach, Lizaveta 1982- (Central European University Press, 2023)
"The proclamation of Belarusian independence on March 25, 1918, and the rival establishment of the Soviet Belarusian state on January 1, 1919 created two distinct and mutually exclusive national myths, which continue to define contemporary Belarusian society. This book examines the processes that resulted in this dual resolution in the context of the First World War and the subsequent Russian Revolutions. Lizaveta Kasmach scrutinizes a variety of factors that affected the formation of the Belarusian national idea, the role of its protagonists, their complex relationships with the Polish and the Lithuanian counterparts, the impact of the German policy, as well as the Russian imperial and later the Bolshevik governments'' attitude towards the Belarusian national awakening. Based on original archival material, the analysis convincingly demonstrates the divisions within the nationalist movement, both politically between the moderates and socialists, and geographically between German-occupied territory with Vilna as a center versus Russian-controlled territory around Minsk. Besides the case-study of Belarusian nation-building efforts, the book is a contribution to the study of the First World War in East Central Europe, approaching the war and its aftermath as a mobilizational moment in the region"--